Effect of HPPMS Pulse-Frequency on Plasma Discharge and Deposited AlTiN Coating Properties - Stefanie Severin; Muhammad Naveed; Sabine Weiß (Advances in Materials Science and Engineering)
Coatings like TiAlN (titanium content more than 50%) or AlTiN (aluminium content more than 50%) are well established as hard and wear-resistant tool coatings, often prepared by physical vapour deposition (PVD) like arc evaporation or direct current magnetron sputtering (dcMS). With increasing challenges of operating conditions, there is a constant need for improvement of mechanical properties to withstand extreme loading conditions. This can be obtained by a higher amount of ionized sputtered metal atoms during the deposition process. To increase the metal ion flux a high-power pulse magnetron sputtering (HPPMS) was developed. In order to understand the relation between HPPMS process parameters and mechanical properties of the AlTiN coatings, the present study discusses how different pulse-frequencies (for a constant pulse length) influence AlTiN coating structure growth and their mechanical properties. In addition, film deposition rate and phase formation are influenced by altering process parameters like pulse length and frequency. Hence, different pulse-frequencies produce specific coatings with corresponding properties for functional requirements. Based on the established findings, answers to new scientific queries along with the demand to further optimize these coatings for tool applications are required.